(3EOGQI GdTQGA hGdEeOGO (B/s - (3EOQjS, KGHJ YHO GdQMefs; (3GdeQSj, LeGd GdOjf eMeO s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2005)
(3WHjYI hXjaI GdTQGA hGdEeOGO(B- (3OhQI EOGQI GdeTJQjGJ hGdEeOGO aj efXeGJ GdCYeGd(B- (3CgOGa hSjGSGJ hXjaI GdTQGA hGdEeOGO(B- (3GdfhGMj GdJfXjejI dhXjaI GdTQGA(B- (3JMOjO GdEMJjGLGJ GdTQGFjI(B- (3EOGQI eUGOQ GdJhQjO(B- (3EOGQI GdJhRjY GdeGOj(B- (3bVGjG NGUI aj EOGQI GdEMJjGLGJ(B.s
Keywords: (3EOGQI GdeTJQjGJs; (3GdEeOGOs; (3GdTQGAs